Employment Time and the Cyclicality of Earnings Growth - Hoffmann, Eran (IMF Working Papers; Working Paper, 2018)
We study how the distribution of earnings growth evolves over the business cycle in Italy. We distinguish between two sources of annual earnings growth: changes in employment time (number of weeks of employment within a year) and changes in weekly earnings. Changes in employment time generate the tails of the earnings growth distribution, and account for the increased dispersion and negative skewness in the distribution of earnings growth in recessions. In contrast, the cross-sectional distribution of weekly earnings growth is symmetric and stable over the cycle. Thus, models that rely on cyclical idiosyncratic risk, should separately account for the employment margin in their earnings process to avoid erroneous conclusions. We propose such a process, based on the combination of simple employment and wage processes with few parameters, and show that it captures the procyclical skewness in changes in earnings growth and other important features of its distribution.